Length-weight relationship and condition factor of Liza macrolepis (Smith) from polluted and unpolluted waters of Visakhapatnam - Sandhya, V; Shameem, U (Indian Journal of Fisheries, 2011)
Length-weight relationship was estimated for 730 fishes of Liza macrolepis,collected from unpolluted waters of Gosthani estuary (319) and polluted watersof Visakhapatnam Harbour (411). The results of the study indicated a highregression coefficient value (b) for mullets collected from unpolluted waters ascompared to those from polluted waters, the regression equations beingLog W = -17.551 + 3.6811 Log L (r = 0.7804) and Log W = -5.8171 + 2.0656 LogL (r = 0.80609) respectively. Studies on relative condition factor indicated highermean Kn values in the fishes of unpolluted waters than of polluted waters. Thepresent study indicates that the growth and condition of the fish is affected bythe prevailing environmental conditions of the polluted waters